The concept of zuhd (asceticism) in education: an Islamic reformulation of levinson theory seasons of life - Ismail, Nik Ahmad Hisham (s.n, 2012)
Psychology is one of the important disciplines that related to the whole life of human being, its major concern is study of man and what affects him. But the present days psychologists does not realize the fact that human being is created by a supreme being, who knows everything about man and all that surround him. It should be noted that whoever knows the origin of an object is in the best position to give accurate account and precise description about the object, which shows that the issue of religion is an inseparable element from the discipline of psychology. Therefore integrating Islamic ideals to the stream of psychology is the most important responsibility of Muslim psychologists, Hence this study centered on how the Islamic concept of zuhd will reformulate the Levinson theory of seasons of life. The study employs qualitative design in order to have profound and clear meaning of the Islamic concept of zuhd.